Bacteria in agrobiology plant growth responses - Maheshwari, Dinesh K. (Springer eBooks., 2011)
The future of agriculture strongly depends on our ability to enhance productivity without sacrificing long-term production potential. An ecologically and economically sustainable strategy is the application of microorganisms, such as the diverse bacterial species of plant growth promoting bacteria (PGPB). The use of these bio-resources for the enhancement of crop productivity is gaining worldwide importance. Bacteria in Agrobiology: Plant Growth Responses describes the application of various bacteria in plant growth promotion and protection, including symbiotic, free living, rhizospheric, endophytic, methylotrophic, diazotrophic and filamentous species.